Preparation and characterization of polylactide/polycaprolactone/fatty hydrazide and octadecylamine-modified clay nanocomposite - Hairaldin, Siti Zulaiha (2012)
In this study, two organically modified montmorillonite (OMMT) clay were prepared via ion exchange reaction. One was fatty hydrazides synthesized from palm oil functions was use to modify the nature of montmorillonite (Na-MMT). The other was ODA which is obtained from the industry. FH-MMT and ODAMMT organoclay were successfully prepared by intercalation of the alkylammonium chains into the gallery of MMT via ion exchanged reaction. The basal spacing of FH-MMT and ODA-MMT has increased from the original Na-MMT of 11.62Å to 13.10 Å 29.90 Å respectively. The shifting of the basal peak position indicates successfully intercalation of alkylammonium ion into the modified clay. Fourier Transform Infrared (FTIR) spectra of the FH-MMT and ODA-MMT organoclay indicated that the presence of alkylammonium ion group resulting from modification reaction. The 90/10 of PLA/PCL ratio nanocomposites was chosen to produce PLA/PCL nanocomposite in the internal mixer. This was chosen due to the highest tensile strength among PLA/PCL blends besides severe loss in elongation at break. Furthermore, TGA result indicated ratio 90/10 increase about 27 oC and 72 oC of maximum thermal degradation temperature (Tmax) and decomposition temperature (Td) compared to neat PLA. Two types of nanocomposites were prepared by melt blending technique and characterized. The X-ray diffraction (XRD) technique was used to analyze the degree of expansion of the prepared clays. XRD analysis indicated that PLA/PCL containing 1, 3, 5, 7, and 10% FH-MMT exhibits interlayer distance of 13.26, 13.80, 13.93, 14.31, and 14.06 Å respectively. Meanwhile, the d001 diffraction for PLA/PCL containing 1, 3, 5, 7% ODA-MMT exhibits interlayer distance of 30.87, 31.14, 32.24 and 32.34 Å respectively. The transmission electron microscopy (TEM) was used to confirm the presence of the clay. The presence of intercalated and partially exfoliated structure for nanocomposites was observed. The clay was dispersed however the agglomeration in the TEM micrograph was still exist. The thermal stability of PLA/PCL improved after addition of FH-MMT and ODA-MMT. Presence of 1% of FH-MMT in PLA/PCL improved about 24 oC and 17 oC compared to neat PLA/PCL in term of the maximum thermal degradation temperature (Tmax) and initial degradation temperature (T on) respectively.